WHAT DO WE KNOW ABOUT ADULT MAMMALIAN HIPPOCAMPAL NEUROGENESIS SO FAR? - Jeremic, Rada; Pekovic, Sanja; Dacic, Sanja; Brkic, Predrag (Medicinski podmladak, 2023)
Now it is known that the adult mammalian brain can add new neurons throughout the whole lifespan. Neuronal stem cells reside in the subgranular zone of the dentate gyrus of the hippocampus and the subventricular zone of the rostral lateral ventricle. Neuronal stem cells in the subgranular zone give the excitatory granular cells of the dentate gyrus, and in the subventricular zone give new interneurons that migrate to the olfactory bulb.The following review will focus on characteristics of adult mammalian neurogenesis in the hippocampus. Also, we will try to discuss still the active question about the existence of adult neurogenesis in humans.According to numerous studies, adult neurogenesis in the dentate gyrus enhances neuronal plasticity. Type 1 cells in the dentate gyrus, so-called radial glial-like cells, undergo rapid division and produce intermediate progenitor cells (type 2a and type 2b), which can proliferate, and differentiate. Type 2b become neuroblasts (type 3 cells), which migrate, differentiate, and maturate into granular cells. These cells can be identified by location, morphology, and expression of different markers on their surface.Despite earlier evidence pointing to the existence of adult neurogenesis in humans, recent studies on this topic showed contradictory results, one in favor and the other against it. Even though adult neurogenesis is proven in distinct species, we still do not know whether differences between species exist. The exact conditions necessary for the proper development of adult neurogenesis and the factors that can influence it are still unrevealed and we have to examine them. Human adult neurogenesis remains an open question.
Keywords: adult neurogenesis, hippocampus, dentate gyrus, subgranular zone